Bilobetin Shows Immunomodulatory and Chemopreventive Activities in Benzo(a)pyrene-Induced Lung Cancer in Mice Model - Xu, Zhenjie; Zhu, Lihuan; Wang, Shentao (Indian Journal of Pharmaceutical Education and Research, 2018)
Background: Lung cancer, a malignancy resulting from the uncontrolled growth of cells in pulmonary tissues, remains to be a primary cause of cancer-associated deaths worldwide, requiring a thorough understanding of its complex pathophysiology to develop effective treatment techniques. Objectives: The present work was aimed at analyzing the anticancer properties of the bilobetin against benzo(a)pyrene (B(a)P)-induced lung cancer in mice. Materials and Methods: Lung cancer was induced in mice with oral treatment of B(a)P for four consecutive weeks (from second to sixth week). Bilobetin (25 mg/kg) was provided to the mice one week prior to and throughout the 16 weeks via oral gavage. The concentrations of phase-I and -II detoxifying enzymes, immunoglubulins (Igs), and xenobiotic dysfunction markers were assessed in the experimental mice. The concentrations of tumor biomarkers, pro-inflammatory cytokines, and other tumor-related molecular markers were assessed using respective diagnostic kits. The inflammatory cells and phagocytic and avidity indexes were also evaluated in the experimental mice. Results: The present results evidenced that the treatment of 25 mg/kg of bilobetin significantly regulated the concentrations of phase-I and -II enzymes, Igs levels, and reduced the xenobiotic dysfunction markers in B(a)P-induced mice. Moreover, the bilobetin considerably decreased the tumor biomarker levels, inflammatory cytokine levels, and increased the inflammatory cells in B(a)P-treated mice. The concentrations of PCNA, NF-κB, CYP1A1, and NRF-2 was considerably reduced by the bilobetin treatment in the B(a)P-treated mice. Conclusion: Our results demonstrate that bilobetin treatment exhibits immunomodulatory and chemopreventive properties in lung cancer in mice. Consequently, it was evident that bilobetin treatment possesses immunomodulatory and chemopreventive properties against lung cancer and may enhance chemotherapy approaches for lung cancer.
Keywords: Cytochrome P450; Immunoglobulins; Glutathione-S-transferase; Bilobetin; Lung; cancer